Customizing a Li–metal battery that survives practical operating conditions for electric vehicle applications. Issue 7 (7th June 2019) - Hwang, Jang-Yeon; Park, Seong-Jin; Yoon, Chong S.; Sun, Yang-Kook
Abstract : We customized a combination of cathode, anode, and electrolyte to develop an LMB capable of cycling both at a high loading capacity and at a high current density that satisfy the capacity and charging rate requirements for future electric vehicles. Abstract : We propose a new breakthrough in realizing a practical Li–metal battery (LMB) capable of fast charging while delivering a high energy density. We used an electrolyte consisting of 1 M LiPF6 and 0.05 M lithium difluoro(oxalate)borate dissolved in a mixture of ethyl methyl carbonate and fluoroethylene carbonate to ensure the formation of a stable and robust solid electrolyte interphase (SEI) layer on the anode surface. Pretreatment of the Li–metal anode with LiNO3 adds a prior Li2 O-rich SEI layer that provides the required mechanical strength to prevent premature SEI layer breakdown. An Al-doped full-concentration-gradient Li[Ni0.75 Co0.10 Mn0.15 ]O2 cathode provides the necessary cycling stability at a high cathode loading. By integrating these components, we produced an LMB that allowed a high areal capacity of 4.1 mA h cm −2 with an unprecedented cycling stability over 300 cycles at a high current density of 3.6 mA cm −2 (full charge–discharge in 2 h). We believe that the findings presented herein provide new perspectives for the development of practical LMBs that satisfy the capacity and charging rate requirements for future electric vehicles.